Computer host with mistaken touch prevention structure - XIAO HONGWEI; DAI BOTAO; HUANG XINXIA; ZHOU XIANJING (2023)
The utility model belongs to the field of computer hosts, in particular to a computer host with a mistaken touch prevention structure, which comprises a host main body, the left end and the right end of the host main body are respectively provided with a mounting groove, the front wall and the rear wall of each mounting groove are respectively provided with two slots, and the two mounting grooves are respectively connected with a heat dissipation and dust blocking mechanism through the slots in an inserted manner. The front end of the host body is fixedly connected with a protection seat, the right wall of the protection seat is provided with an insertion groove, the front end of the protection seat is provided with a plurality of notches, the upper walls and the lower walls of the notches are fixedly connected with wire clamping mechanisms, and the opposite surfaces of the two heat dissipation and dust blocking mechanisms are fixedly connected with concave seats. According to the computer host with the mista